Bioactive Compounds in Aqueous Extract of Pilis, A Forehead Transdermal Herbal Medicine - Timotius, Kris Herawan; Sudrajat, Susana Elya; Rahayu, Ika (Pharmacognosy Communications)
Introduction: Pilis is a traditional Javanese transdermal herbal formula applied on the forehead to cure dizziness, hazy vision, eyestrain, and fever. So far, there are no scientific report on the bioactive compounds of the aqueous extract of pilis. This study aimed to identify the main bioactive compounds in the aqueous extract of pilis, either fresh-made or commercial pilis. Then, the bioactivities of the identified bioactive compounds were described based on the relevant literature studies. Materials and Methods: LC-MS was used to analyze the aqueous extracts of various pilis. Relevant information on their bioactivity is available from the works of the literature. Results: The identified main bioactive compounds in the aqueous extract of pilis were: undulatoside A, viscumneoside II, kaempferol, quercetin, genistein, and 7-hydroxy 5,8-dimethoxyflavone. Most compounds were in glycosidic form. The fresh-made pilis was more abundant in the number of bioactive compounds than the commercial pilis. Their bioactivities include antioxidant, anti-inflammation, neuroprotective, anti-cancer, and anti-microbial activities. Conclusion: Aqueous extracts of pilis, particularly fresh-made pilis, are promising transdermal forehead formulas rich in particular bioactive compounds with healing capacities to cure encephalitis and dizziness.
Keywords: Dizziness; Encephalitis; Mother after birth; Overhead; Transdermal